1999
DOI: 10.1046/j.1365-8711.1999.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar rotation measures and the magnetic structure of our Galaxy

Abstract: We have obtained 63 rotation measures (RMs) from polarization observations of southern pulsars, of which 54 are new measurements and 3 are varied from previous values. The new pulsar RM data at high Galactic latitudes are mostly consistent with the antisymmetric RM distribution found previously. For the Galactic disc, evidence for a field reversal near the Perseus arm, and possibly another beyond it, is presented. Inside the Solar Circle, in addition to the two known field reversals in or near the Carina-Sagit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
281
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(302 citation statements)
references
References 57 publications
20
281
1
Order By: Relevance
“…In the early days, using a few tens of RMs, we found B z ∼ 0.2μG (Han & Qiao 1994, Han et al 1999b. Recent extensive observations have resulted in a much improved RM dataset (Mao et al 2010) which more or less confirmed the existence and the strength of such a vertical field.…”
Section: Magnetic Fields In the Galactic Halomentioning
confidence: 77%
See 2 more Smart Citations
“…In the early days, using a few tens of RMs, we found B z ∼ 0.2μG (Han & Qiao 1994, Han et al 1999b. Recent extensive observations have resulted in a much improved RM dataset (Mao et al 2010) which more or less confirmed the existence and the strength of such a vertical field.…”
Section: Magnetic Fields In the Galactic Halomentioning
confidence: 77%
“…The vertical fields in the Galactic center naturally act as the poloidal fields in such a field configuration. Although the scale radius and scale height for such halo toroidal fields are not yet known, and more seriously little is known about the electron density distribution in the halo, this qualitative toroidal halo field model derived from the antisymmetric RM sky (Han et al 1997, Han et al 1999b) has now widely been adopted in many quantitative models (e.g. Sun et al 2008) since the first parametrization by Prouza † Rotation measure synthesis is probably not a good tool to separate the diffuse emission from different regions along a sightline at different distances with different polarization properties and different foreground Faraday rotations.…”
Section: Magnetic Fields In the Galactic Halomentioning
confidence: 99%
See 1 more Smart Citation
“…From the RM distribution in the sky, Han et al (1997Han et al ( , 1999 identified the striking antisymmetry in the inner Galaxy with respect to the Galactic coordinates after removing the RM "outliers" compared to their neighborhoods. Such an antisymmetry should be a result from the azimuthal magnetic fields in the Galactic halo with reversed field directions below and above the Galactic plane.…”
Section: The Galactic Magnetic Fields On Large Scalesmentioning
confidence: 99%
“…The observed filaments near the Galactic center should result from the dipole field in this dynamo scenario. The local vertical field component of 0.2 µG (Han & Qiao 1994, Han et al 1999) may be part of this dipole field in the solar vicinity. At present, we have observed another 1700 radio sources in the Northern sky by the Effelsberg 100 m telescope (Han, Reich et al 2007, in preparation), and we wish to do more in the Southern sky at Parkes, so that the RM sky can be described quantitatively.…”
Section: The Galactic Magnetic Fields On Large Scalesmentioning
confidence: 99%